Recurrent chalazia secondary to bortezomib - Fatin Hanisah F,; Rona Asnida Nasaruddin,; Jemaima Che Hamzah, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Few cases of chalazia secondary to bortezomib are reported in literature. However, it is not a recognized ocular adverse effect. We hereby report a case of recurrent chalazia secondary to bortezomib. A 40-year-old male with light chain myeloma on ten weeks of chemotherapy with bortezomib was treated for left eye inflamed chalazion with bilateral meibominitis. Severe chalazia persisted despite treatment, which necessitated cessation of chemotherapy. The patient’s condition improved on oral doxycycline and chemotherapy was recommenced but his chalazia recurred, necessitating incision and curretage. His chalazia responded to oral azithromycin without further cessation of chemotherapy. Bortezomib’s association with chalazia has been characterized as a possible adverse drug reaction according to the World Health organization classification, and its recognization as an established adverse reaction to will allow earlier identification and appropriate co-management of the patient.